Agriculture and irrigation water policies toward improved water conservation in Jordan - Shatanawi M.; Duqqah M.; Naber S. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
The paper addresses the water situation in Jordan in term of supply and demand management as well as policy formulation and implementation in irrigation and irrigated agriculture. Specific policies has been formulated to ensure sustainability of irrigated agriculture, optimal utilization of water resources, maximizing water efficiencies and optimization economic return of unit volume of water. The policies of Ministry of Water and irrigation and the policy of the Ministry of Agriculture have been translated into action plans and projects. It seems that these projects are being harmonized by both entities to meet the objective goal aiming at water saving in the agricultural sector. The level of policy implementation in both sectors is satisfactory although additional efforts are needed in term of human resources development and training of farmers. The papers present some projects and success cases in promoting water saving and increasing efficiencies and water productivity.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)